Dynamics of the modulated electron beam in the inhomogeneous plasma barrier: one-dimentional simulation using PIC method - Anisimov, I.O.; Soloviova, M.J. (Вопросы атомной науки и техники, 2008)
Evolution of the modulated electron beam moving through the plasma barrier was studied via computer simulation using PIC method. Inhomogeneous plasma barrier with parameters corresponding to experimental conditions [1-2] was studied. Dependencies of the maximal signal amplitude and coordinate of this maximum at the modulation frequency upon the initial beam modulation depth were obtained. Simulation results were compared with experimental results and outcomes of the previous simulations. Досліджено еволюцію модульованого електронного пучка в плазмовому бар’єрі шляхом комп’ютерного моделювання методом крупних частинок. Розглядається неоднорідний плазмовий бар’єр, що відповідає умовам лабораторного експерименту. Отримано залежності максимального значення амплітуди сигналу на частоті модуляції та положення даного максимуму від початкової глибини модуляції. Результати моделювання співставлено з експериментальними даними та результатами попередніх моделювань. Исследуется эволюция модулированного электронного пучка в плазменном барьере с помощью компьютерного моделирования методом крупных частиц. Рассматривается неоднородный плазменный барьер, соответствующий условиям лабораторного эксперимента. Получены зависимости максимальной амплитуды сигнала на частоте модуляции и положения данного максимума от начальной глубины модуляции. Результаты моделирования сопоставлены с экспериментальными данными и результатами предшествующих моделирований.